Learning Orientation Program Social Mobility Communication for Blind Students at SLBN Tasikmalaya - Chaidir, Ainun; Aprilia, Imas Diana; Susetyo, Budi (Angstrom Centre of Education, 2024)
This research aims to describe the design and implementation of a special communication social mobility orientation program for blind students in SLBN Tasikmalaya Regency. This research is descriptive research with a qualitative approach. The research subject was one blind student. Data collection techniques were carried out by interviews and observation. Data analysis was carried out using reduction, data display, and conclusion drawing/verification. The research results show that the preparation stage was carried out by carrying out identification, assessment, analyzing the curriculum and compiling teaching modules. The teaching module includes three activities, namely introductory activities, core activities and closing activities. Preliminary activities contain activities to motivate, focus attention and find out the abilities that students have mastered. In core activities, the teacher uses lecture and demonstration methods. The teacher uses clothing brought by the students. In the closing activity, an assessment is carried out. At the evaluation stage, the teacher carries out formative evaluations during the learning process and after learning. Evaluation is carried out by observation and practical tests. Recommendations for further research are to carry out intervention efforts to improve the quality of learning, such as making innovations in media, teaching materials and assessments.